Ukuran Perusahaan, Resiko Bisnis, dan Growth Opportunity sebagai Faktor Penentu Struktur Modal - Aisya Augestaryani; Dyah Utari Ratnaning Andini; Dwi Lesno Panglipursari (Kampus Akademik Publiser, 2024)
This study aims to examine and analyze the effect of Ukuran perusahaan, Business Risk, and Growth Opportunity on capital structure. The research object used was a manufacturing sector that consumed the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2020-2023. This study uses a purposive sampling technique in determining research samples. The number of companies selected as research samples is 10 companies from 26 companies registered in the consumer goods sector. This research includes the type of explanatory research using a quantitative approach. The data analysis method used in this study is multiple linear regression analysis. Research results show that simultaneous Ukuran perusahaan, Business Risk, and Growth Opportunity have a significant effect on capital structure. While partially ukuran perusahaan and growth opportunity have no significant effect on capital structure, and business risk has a significant effect on capital structure.